The Influence of Online Learning Platforms on Early Childhood Education and Its Role in Promoting Sustainable Global Economic Growth - Hamzat, Baniyaminu Opeyemi (Journal of Early Childhood Development and Education, 2025)
Abstract:Background of the Study: Online learning platforms have become increasingly relevant in early childhood education, particularly in the context of advancing global educational equity and preparing a skilled future workforce. Aims and Scope of the Paper: The purpose of this study is to investigate the impact of online learning platforms on early childhood education and their role in promoting sustainable global economic growth. Methods: The study employed a quasi-experimental design with a pretest-posttest control group. A sample of 80 pupils from Olorunda Local Government area of Osun State was selected, divided into an experimental group (40 pupils) using online learning platforms and a control group using traditional learning methods. The instruments were validated by experts and tested for reliability through a pilot study, yielding a Cronbach’s alpha of 0.82, indicating good internal consistency. Data were collected using a cognitive development assessment tool, an engagement and motivation survey. Results: The results indicated a statistically significant improvement in cognitive development scores for the experimental group using online platforms (M = 75.25, SD = 8.67) and the control group (P = .037). Conclusion: The positive impact of these platforms underscores the potential for technology to transform early childhood education and support a sustainable global economy by building a more educated and skilled future workforce. Keywords: Cognitive Development, Early Childhood Education, Economic Growth, Engagement and Motivation, Online Learning Platforms